Magnetic resonance imaging assessment of the therapeutic effect of combined electroacupuncture and stem cells in acute peripheral nerve injury - Chen, Yueyao; Pan, Zhongxian; Meng, Fanqi; Yu, Xuewen; Xu, Qian; Huang, Leyu; Liang, Qiumei; Wu, Yanglei; Lin, Xiaofeng (Frontiers in Cellular Neuroscience, 2022)
Mesenchymal stem cells (MSCs) transplantation and Electroacupuncture (EA) were promising strategies for the treatment of peripheral nerve injury (PNI), but the efficacy of their combination was unknown. Magnetic resonance imaging (MRI) is considered an attractive and clinically translatable tool for longitudinal tracking of nerve repair in vivo. In this study, we used parameters derived from MRI to evaluate the therapeutic effect of a combination of MSCs and EA in rat acute sciatic nerve crush injury. Rats were randomly divided into the MSCs+EA group, MSCs group, EA group, and PBS group (control). Electroacupuncture was performed on a rat receiving EA treatment at Huantiao (GB30) and Zusanli (ST36). T2 values and diffusion tensor imaging (DTI) derived from multiparametric magnetic resonance imaging (MRI), histological assessments, and immunohistochemistry were used to monitor nerve regeneration. Walking track analysis was used to assess nerve motion functional recovery. Immunofluorescence staining for axon guidance molecule Netrin-1 revealed that it was significantly higher in the EA+BMSCs subgroup and EA subgroup than it was in the control (PBS) subgroup at 1-3 weeks. Immunofluorescence staining for S100 showed the continuity of nerve fibers recovered more quickly in EA+BMSCs subgroup than in BMSCs subgroup. Our research revealed that a combination of MSCs and EA can provide both topological and biomolecular guidance to promote axonal extension, myelin regeneration, and functional recovery after PNI. EA not only promotes nerve repair on its own, but also enhanced the beneficial effects of stem cell treatment and the secretion of Netrin 1, a guidance regeneration factor, and promotes the orderly growth of nerve fibers. These PNI repairs could be monitored non-invasively and in situ by MRI. The FA and RD values derived from MRI could be sensitive biomarkers to reflect PNI repair process.